Comparative Evaluation of Target-Controlled Infusion versus Syringe Pump Bolus for Remifentanil Administration on the Incidence of Apnoea and Bradycardia during General Anaesthesia Induction: A Double-Blind Pilot Randomised Controlled Trial - Ardhana Surya Aji; Bambang Novianto Putro; Andy Nugroho (HM Publisher, 2026)
Remifentanil is widely utilized during general anaesthesia induction to attenuate adverse haemodynamic responses to tracheal intubation. However, its profound analgesic efficacy is inherently linked to dose-dependent adverse effects, primarily opioid-induced respiratory depression (apnoea) and bradycardia. This pilot study evaluates the safety profile of pharmacokinetically guided target-controlled infusion (TCI) compared to conventional syringe pump (SP) bolus administration. A double-blind, pilot randomised controlled trial was conducted involving 36 ASA I–II patients undergoing elective maxillofacial surgery. Patients received a standardized co-induction of propofol (2.0 mg/kg), followed by remifentanil via SP (1 µg/kg over 60 seconds) or TCI (initial effect-site concentration [Ce] of 6 ng/mL for 5 minutes, reduced to 4 ng/mL). Primary outcomes were the incidence of apnoea (>15 seconds) and bradycardia (<50 bpm). Apnoea occurred in 33.3% of the SP group versus 16.7% in the TCI group (RR 2.00; p=0.222). Mean onset of apnoea was 41.0±11.0 seconds (SP) and 31.0±3.6 seconds (TCI) (p=0.085). Bradycardia was observed in 72.2% of the SP cohort and 50.0% in the TCI cohort (RR 1.44; p=0.153). All bradycardic events were transiently managed with 0.5 mg of atropine. In conclusion, in this pilot cohort, remifentanil delivered via TCI did not achieve statistical superiority over SP bolus administration in reducing the incidence of apnoea or bradycardia. Fully powered clinical trials are required to definitively establish any pharmacokinetic safety advantages.